2001
DOI: 10.1163/156853701300063589
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Non-natural Concepts: The Role of Intuitive Conceptual Structures in Memory and Transmission of Cultural Materials

Abstract: The four experiments presented support Boyer's theory that counterintuitive concepts have transmission advantages that account for the commonness and ease of communicating many non-natural cultural concepts. In Experiment 1, 48 American college students recalled expectation-violating items from culturally unfamiliar folk stories better than more mundane items in the stories. In Experiment 2, 52 American college students in a modi ed serial reproduction task transmitted expectation-violating items in a written … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(86 citation statements)
references
References 25 publications
(13 reference statements)
1
83
0
2
Order By: Relevance
“…For example, ghosts have human-like intentions (a folk psychology module) but in being able to pass through solid objects violate another (a folk-physics module). The aforementioned study by Barrett & Nyhof (2001) supports this claim, with population-level consequences of this bias seen in the widespread popularity of supernatural or religious beliefs across the world (Boyer 1994) and the persistence of minimally counter-intuitive folk tales through history (Norenzayan et al 2006).…”
Section: The Linear Transmission Chain Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…For example, ghosts have human-like intentions (a folk psychology module) but in being able to pass through solid objects violate another (a folk-physics module). The aforementioned study by Barrett & Nyhof (2001) supports this claim, with population-level consequences of this bias seen in the widespread popularity of supernatural or religious beliefs across the world (Boyer 1994) and the persistence of minimally counter-intuitive folk tales through history (Norenzayan et al 2006).…”
Section: The Linear Transmission Chain Methodsmentioning
confidence: 83%
“…Transmission chain studies, in which information is passed along linear chains of participants, show that human cultural transmission can often be vulnerable to distortions and biases rather than constituting a process of high-fidelity replication. These studies have identified several candidate content biases in cultural transmission: a counter-intuitive bias (Barrett & Nyhof 2001); a hierarchical bias ); a gender-stereotype bias (Bangerter 2000;Kashima 2000); and a social bias (Mesoudi et al 2006a). (We qualify these as 'candidate' biases given that each is supported by one or at most two experiments; as the field expands, we anticipate future experiments to provide further support or qualifications to these initial findings.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesoudi, Whiten, & Dunbar, 2006;Stubbersfield, Tehrani, & Flynn, 2015); iii) a bias for emotionally arousing content, such as disgust, or amusement (Eriksson & Coultas, 2014;Stubbersfield, Tehrani, & Flynn, 2017); iv) a bias for minimally-counterintuitive (MCI) information that violates some of our implicit ontological assumptions about the world in ways that makes it more salient than information that can either be taken-for-granted or is incomprehensible (e.g. Barrett & Nyhof, 2001); v) a stereotype-consistency bias, in which information is transformed and recalled in ways that make it more consistent with pre-existing expectations and prejudices (e.g. Bangerter, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%